Outcomes of Neoadjuvant Chemoradiation With and Without Systemic Chemotherapy in Resectable and Borderline Resectable Pancreatic Adenocarcinoma - Trinh, Katherine V.; Fischer, Dawn A.; Gardner, Timothy B.; Smith, Kerrington D. (Frontiers in Oncology, 2020)
Introduction Neoadjuvant therapy is increasingly being used for localized pancreatic adenocarcinoma. While there is evidence supporting neoadjuvant systemic chemotherapy as well as chemoradiation, more evidence is needed to determine whether systemic chemotherapy with chemoradiation offers benefits over chemoradiation alone. This study compares the outcomes of neoadjuvant chemoradiation therapy with and without systemic chemotherapy in resectable and borderline resectable pancreatic cancers. Methods This retrospective study evaluated patients with resectable and borderline resectable pancreatic adenocarcinoma who completed neoadjuvant chemoradiation therapy with and without systemic chemotherapy prior to surgical resection. 149 patients met inclusion criteria, with 75 having resectable cancer and 74 having borderline resectable cancer. Outcomes included recurrence free and overall survival rates at 6, 12, and 36 months. Results In resectable pancreatic carcinoma, 72% of patients treated with chemoradiation alone achieved 1 year recurrence free survival compared to 78% of patients treated with systemic chemotherapy and chemoradiation (p=0.55). 28% of patients treated with chemoradiation alone had 3 year recurrence free survival compared to 31% of patients who received systemic and chemoradiation therapy (p=0.75). In both treatment groups, 92% of patients lived past 1 year (p=0.92), and 44% of patients survived at least 3 years (p=0.95). In borderline resectable pancreatic carcinoma, 50% of patients treated with chemoradiation alone achieved 1 year recurrence free survival compared to 70% of patients treated with systemic chemotherapy and chemoradiation (p=0.079). The 3 year recurrence free survival was 26% and 29% for the chemoradiation alone group and the systemic chemotherapy plus chemoradiation group respectively (p=0.85). There was no significant difference in 1 year overall survival: 85% of patients treated with chemoradiation alone survived compared to 92% of patients treated with systemic chemotherapy and chemoradiation (p=0.32). Both groups had 41% 3 year overall survival (p=0.96). Discussion In resectable and borderline resectable pancreatic adenocarcinoma, there was no significant difference in overall or recurrence free survival between patients treated with chemoradiation with and without systemic chemotherapy. Our findings suggest that systemic neoadjuvant chemotherapy with chemoradiation and chemoradiation alone are efficacious treatments for localized pancreatic carcinoma. This brings into question whether more effective systemic chemotherapy is necessary to increase survival benefit.